Graduate students as preceptors: Effects on clinical teaching outcomes of medical nursing - Lu Lin; Yun-Ying Hou; Xiao-Hua Wang; Yan-Xia Han (Elsevier, 2014)
Purpose: To explore the feasibility of using graduate students as preceptors in the clinical education of medical nursing students. Methods: Five second-year graduate nursing students were recruited to participate in the clinical teaching of medical nursing for 38 undergraduates in the first semester of the 2010-2011 academic year, divided into two groups. The first group first received clinical teaching in caring for respiratory diseases from graduate preceptors for six weeks followed by clinical teaching in caring for circulatory diseases from nurse preceptors for six weeks. The second group received clinical teaching in the reverse order, from the nurse preceptors followed by the graduate student preceptors. Following training, all students were examined with a written test and scores were compared. In addition, review meetings were held to evaluate the teaching outcomes. Results: No significant differences in test scores were observed between the two teaching groups. Undergraduate student feedback indicated that the training provided by the graduate students was satisfactory, and the medical nursing course leader was satisfied with the teaching outcome with a few exceptions. Conclusion: These data indicate that graduate students are capable of training undergraduates in medical nursing, although some areas can be improved.